1985
DOI: 10.1177/33.4.3980981
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of elements in cells and matrix of epiphyseal growth plate cartilage determined by quantitative electron probe analysis.

Abstract: Quantitative electron probe analysis was performed on chick epiphyseal growth cartilage prepared by two anhydrous methods, ultrathin cryosections and freeze-dried epoxy-embedded tissue. Levels of Na, Mg, P, S, Cl, K, and Ca were determined in cytoplasm, mitochondria, extracellular matrix, matrix vesicles, and mineral nodules in four zones of the cartilage--proliferative, prehypertrophic, early hypertrophic, and early calcification. The exceptionally high levels of Na and K (up to 550 and 200 mmol/kg wet wt, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Previous in vitro studies have suggested that proteoglycan monomers and aggregates inhibit calcification or mineral formations of calcium and phosphate (Cuervo et al 1973;Blumenthal et al 1979;Chen et al 1984;Dziewiatkowsky and Majznerski 1985). On the other hand, other investigators have shown that there is no detectable drop in concentration of proteoglycans in the cartilage matrix of the growth plate which will calcify or has already calcified (Poole et al 1982a;Scherft and Moskalewski 1984;Hargest et al 1985;Poole et al 1989). Poole and co-workers demonstrated immunohistologically that the immunoreaction for proteoglycan monomer core protein and link protein even increased in the calcified cartilage (Poole et al 1982a).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies have suggested that proteoglycan monomers and aggregates inhibit calcification or mineral formations of calcium and phosphate (Cuervo et al 1973;Blumenthal et al 1979;Chen et al 1984;Dziewiatkowsky and Majznerski 1985). On the other hand, other investigators have shown that there is no detectable drop in concentration of proteoglycans in the cartilage matrix of the growth plate which will calcify or has already calcified (Poole et al 1982a;Scherft and Moskalewski 1984;Hargest et al 1985;Poole et al 1989). Poole and co-workers demonstrated immunohistologically that the immunoreaction for proteoglycan monomer core protein and link protein even increased in the calcified cartilage (Poole et al 1982a).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the distribution in the different layers and compartments in cartilage. It has been demonstrated that the proportion of divalent cations vary between different layers in epiphyseal growth cartilage (49), scapular growth cartilage (52), and in adult articular cartilage (47). This distribution is likely to be influenced by the molecular composition of the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusions such as these have been reported in abnormal cartilage from humans (Hwang et al, 1982). Although there are no reports of similar inclusions observable by light microscopy in avian cartilage, dilated segments of rough endoplasmic reticulum have been observed ultrastructurally in avian physeal cartilage (Hargest et al, 1985a;Howlett, 1979;Kashiwa et al, 1975;Lutfi, 1974) and in murine cartilage (Schofield, 1975). A possible explanation for the lack of reports describing cytoplasmic inclusions at the light microscopical level in avian tissues is that they may have been overlooked.…”
Section: Discussionmentioning
confidence: 91%